Optimization, Characterization, and Antioxidant Activity of Sunflower Oil-Based SNEDDS using Response Surface Method - Rodhia Ulfa; Gressy Novita; Sella Asharianti (Journal of Food and Pharmaceutical Sciences, 2026)
This study aims to optimize, characterize, and evaluate the antioxidant activity of sunflower seed oil-based SNEDDS using Tween 80 and PEG 400. The study utilizes Simplex Lattice design and Response Surface Methodology to obtain a formula with the best physical characteristics and efficacy. Sunflower seed oil was selected due to its high content of essential fatty acids and antioxidants. The optimization method involved determining the ratio of surfactant, cosurfactant, and oil, as well as characterization tests of particle size, polydispersity index, zeta potential, emulsification time, and antioxidant activity. The results showed an optimal formula with a nano particle size of 13 nm ± 0.346, low polydispersity index (0.161 ± 0.067), and zeta potential of -21.8 mV ± 0.577, ensuring physical stability. The antioxidant activity of SNEDDS remained high with an IC50 of 18.06 μg/mL. Formulation verification through statistical analysis confirmed the consistency of experimental results with optimization software predictions. In conclusion, the optimized sunflower seed oil SNEDDS offers an innovative oral formulation that is efficient, stable, and safe, with the potential to improve bioavailability, pharmacological activity, and the utilization of local vegetable oils in modern pharmacy.